1993
DOI: 10.1111/j.1365-2621.1993.tb06083.x
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Processing Affect Color, Metmyoglobin Reductase and Oxygen Consumption of Beef Muscles

Abstract: Color stability and various biochemical properties were determined in bovine longissimus dorsi and psoas major at different times postmortem (8 hr to 21 days) and during retail display. Surface metmyoglobin accumulation, metmyoglobin reductase activity and oxygen consumption rate were affected by muscle type, postmortem aging, and'fabrication method (p < 0.01). Psoas steaks had greater metmyoglobin accumulation, lower metmyoglobin reductase activity, and greater oxygen consumption than longissimus steaks. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 15 publications
5
76
1
Order By: Relevance
“…Several studies have documented the difference between the color stabilities of the beef longissimus and psoas major muscles (O'Keeffe and Hood, 1982;Madhavi and Carpenter, 1993;McKenna et al, 2005;Seyfert et al, 2006;Seyfert et al, 2007;Kim et al, 2009;Mancini et al, 2009;Joseph et al, 2012;Canto et al, 2016). This observed color difference has been attributed to variations in the proportions of muscle fibers present in these 2 muscles (Seyfert et al, 2006).…”
Section: Muscle Sourcementioning
confidence: 98%
See 3 more Smart Citations
“…Several studies have documented the difference between the color stabilities of the beef longissimus and psoas major muscles (O'Keeffe and Hood, 1982;Madhavi and Carpenter, 1993;McKenna et al, 2005;Seyfert et al, 2006;Seyfert et al, 2007;Kim et al, 2009;Mancini et al, 2009;Joseph et al, 2012;Canto et al, 2016). This observed color difference has been attributed to variations in the proportions of muscle fibers present in these 2 muscles (Seyfert et al, 2006).…”
Section: Muscle Sourcementioning
confidence: 98%
“…While some researchers argue that MRA within the muscle is the principal determinant of muscle color stability (Ledward, 1971), others have observed that the reducing activity is of very limited consequence and that OC has more influence on color stability (Atkinson and Follett, 1973;O'Keeffe and Hood, 1982;Renerre and Labas, 1987). Nevertheless, evidence has shown that both reducing activity and OC have an influence on the color stability of muscles (Madhavi and Carpenter, 1993). In contrast, other researchers have suggested that low OC negatively affects color stability as mitochondrial respiration is required to replenish the NADH required for MRA (Sammel et al, 2002).…”
Section: Muscle Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen consumption was determined according to a modified procedure of Madhavi and Carpenter (1993), on the fresh-cut surface of the bottom half portion of the cube removed prior to MRA analysis. The samples were allowed to oxygenate for 30 min at 1°C, vacuum packaged, and then scanned twice (as described in the MRA procedure) on the bloomed surface (representing the previously unexposed interior of the original cube) to measure OxyMb.…”
Section: Oxygen Consumption (Oc)mentioning
confidence: 99%